Effect of nifedipine on contractive motility and ciliary ultrastructure of rabbit fallopian tube - Yang Lin; Xu Yuan-Xiu (Acta Pharmacologica Sinica, 2016)
The effects of nifedipine (Nif) on the motility of isolated isthmus of rabbit Fallopian tube were studied in comparison with those of verapamil (Ver) and cinnarizine (Cin). Nif (0.01 mumol.L-1), Ver (0.03 mumol.L-1), and Cin (3 mumol/L-1) inhibited the spontaneous contraction, and the contraction caused by norepinephrine (NE). The pD'2 values of Nif, Ver, and Cin were 6.86, 6.13, and 4.43, respectively. Moreover, both Nif and Ver delayed the ovum transport through the Fallopian tube 48 h after iv chorionic gonadotropin (HCG). Nif did not modify the ultrastructure of the ampulla ciliary microtubule, but it influenced the mitochondrial structure and caused an irregular ciliary motion.